Hot Deformation Behavior and Microstructural Evolution of Twin-Roll-Casting Mg Alloy during High-Temperature Compression. (18th December 2019) - Yang, Qingshan; Dai, Jiahong; Chai, Sensen; Yu, Daliang; Jiang, Bin; Pan, Fusheng
Abstract : The deformation behavior and microstructural evolution of twin-roll-casting AZ31 Mg alloy sheets were investigated via hot compression tests at 0°, 5°, and 10° from the normal direction. Compression strains of 5%, 15%, 25%, and 35% were employed at high temperatures of 450°C and 500°C. The flow stress as well as the difference in the flow stress associated with different sampling directions decreased when the temperature was increased. Furthermore, the volume fraction of dynamically recrystallized grains increased with increasing deformation, whereas the average grain size decreased. The DRX grain size and the volume fraction of dynamically recrystallized grains increased with increasing deformation temperature. During ultrahigh temperature compression, the effect of sampling direction on the compression microstructure is relatively small.